Health for life - McConnell, Karen E. 1969-; Corbin, Charles B.; Corbin, David E.; Farrar, Terri D. (Human Kinetics, 2014)
A resource that teaches high school students the fundamentals of health and wellness, how to avoid destructive habits and how to choose to live healthy lifestyles. It covers all aspects of healthy living throughout the life span, including understanding health and wellness, and, preventing disease and seeking care